Pengembangan e-Government di Pemerintahan Daerah dalam Rangka Mewujudkan Smart City (Studi di Pemerintah Daerah Kota Malang) - Widodo, Nurjati (Badan Penerbitan Jurnal (BPJ) FIA-UB, 2016)
This study aims to analyze the development of electronic government which is increasingly prevalent in local governance in order to realize smart city. Smart city is a manifestation of a city that provide excellent public services for the community, and create openness to the public by relying on the power of ICT. The concept of smart city has six indicators, namely smart governance, smart economy, smart live, smart living, smart people, and smart mobility. The object of this research is the development of electronic government in the Local Government of Malang City.